Kualitas Kehidupan Kerja, Kecerdasan Emosi dan Efetivitas Tim Kerja dengan Mediator Komitmen Organisasi - Ceria Hermina; Marcham Darokah (Universitas Ahmad Dahlan, 2014)
ABSTRACTThis research identifies the extent of organizational commitment (OC) as mediator variable of quality of work life (QWL), emotional intelligence (EI) and organizational commitment to effective teamwork (ETW) and seeks variables which contribute most to the effective teamwork in the equation models in Nurhidayah Hospital Bantul Yogyakarta. As many as 127 questionnaires were distributed to selected subjects. Data were analyzed by the method of Structural Equation Modeling or SEM using Amos program. The results showed that there is relationship between quality of working life (QWL) and organizational commitment (OC). Quality of working life (QWL) gives 30.5%contribution on organizational commitment (OC). There is relationship between emotional intelligence (EI) and organizational commitment (OC), emotional intelligence (EI) give 12.5% contribution on organizational commitment (OC). There isi relationship between organizational commitments (OC) to effective teamwork (ETW), organizational commitment (OC) gives 97.8% on effective teamwork (ETW). The result shows that organizational commitment (OC) as a mediator variable is able to provide a positive influence on the relationship between the two variables. The result also shows that thare are no releationship between emotional intelligence (EI) and effective teamwork (ETW) (CR:1.96) and relationship between quality of worklife (QWL) and effective teamwork (ETW) CR:1.96).Keywords: effective teamswork, emotional intelligence, quality of work life, organizational commitment.